Fixed Subluxation of the Distal Radioulnar Joint following Malunion of the Ulnar Styloid Process - Brackertz, Sophie; Reissner, Lisa; Fritz, Benjamin; Walker, Jonas; Nagy, Ladislav (Journal of Wrist Surgery, 2022)
Purpose Recent literature on significance and treatment of ulnar styloid fractures suggest that the ulnar styloid is not the central problem but the radioulnar ligaments and their impact on joint stability. However, specifically displaced ulnar styloid process fractures that secondarily heal in an ectopic position remain a rare situation for which diagnostics and treatment options remain a topic of discussion.Methods This case series presents four patients with limited supination due to a fixed dorsal subluxation of the distal radioulnar joint (DRUJ). The reason here fore was a significant malunion of ulnar styloid fracture that was addressed by corrective ulnar styloid osteotomy. Three of these osteotomies used three-dimensional (3D) preoperative planning and patient specific guides.Results All patients presented with a significant displacement of the malunited ulnar styloid fracture (average 32-degree rotation and 5-mm translation). In all four patients, the fixed subluxation of the ulnar head was resolved clinically and radiographically, and the forearm rotation restored after corrective osteotomy of the ulnar styloid and fixation in an anatomical position.Conclusion This case series presents a very specific subset of patients with nonanatomically healed ulnar styloid fractures responsible for a chronic DRUJ dislocation and limited prosupination and its treatment.Level of evidence This is a Level IV, therapeutic study.
Keywords: DRUJ subluxation; fixed pronosupination DRUJ; malunion ulnar styloid process; ulnar styloid fracture